2020
DOI: 10.1177/1758835920971147
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in cancer patients on systemic anti-cancer therapies: outcomes from the CAPITOL (COVID-19 Cancer PatIenT Outcomes in North London) cohort study

Abstract: Background: Patients with cancer are hypothesised to be at increased risk of contracting COVID-19, leading to changes in treatment pathways in those treated with systemic anti-cancer treatments (SACT). This study investigated the outcomes of patients receiving SACT to assess whether they were at greater risk of contracting COVID-19 or having more severe outcomes. Methods: Data was collected from all patients receiving SACT in two cancer centres as part of CAPITOL (COVID-19 Cancer PatIenT Outcomes in North Lond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
(59 reference statements)
0
21
1
Order By: Relevance
“…In contrast with data from a European [ 24 ], and a Chinese study [ 12 ], we found that patients with lung cancer were relatively under-represented being less than a quarter of the study population. The reasons for this are unclear due to the number of patients involved and stochastic effects.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with data from a European [ 24 ], and a Chinese study [ 12 ], we found that patients with lung cancer were relatively under-represented being less than a quarter of the study population. The reasons for this are unclear due to the number of patients involved and stochastic effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Of 20,980 retrieved reports, 42 met study inclusion criteria 28 , 29 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 (Supplementary‐Figure 1). Study authors responded to requests to clarify the numbers and outcomes of IT patients receiving ICI therapy for 13 included reports 28 , 29 , 42 , 43 , 45 , 48 , 49 , 50 , 57 , 61 ,…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] The precise effects of anti-cancer treatments on the course and outcome of SARS-CoV-2 infection are yet to be fully understood, with different reports yielding conflicting results. 5,7,9,10 Understanding of the immune response to SARS-CoV-2 in this heterogeneous population, spanning multiple malignancy types and numerous treatment regimens, is crucial for optimal clinical management of those patients during the ongoing pandemic.…”
Section: Introductionmentioning
confidence: 99%